The structure of entomocomplexes of open biotopes of the Belarusian Polesie in the post-meliorative period - Sergeeva, Tatyana; Lozinskaya, Olga; Smirnova, Elena (Journal of the Belarusian State University. Ecology, 2023)
The assessment of anthropogenically determined dynamics of entomocomplexes, including a number of economically important and biocenotically significant groups of insects inhabiting open biocenoses of the Pripyat floodplain (Belarusian Polesie) has been given. Some patterns in the formation of hortobiont arthropods complexes in natural and transformedhabitats have been established. There have been registered the representatives of 2 classes – insects (Insecta) and arachnids (Arachnoidea) – in the studied territory. The insects are represented by 9 orders (and 22 families): dragonflies (Odonata), orthopterans (Orthoptera), homopterans (Homoptera), semi-coleopterans (Hemiptera), coleopterans (Coleoptera), neuropterans (Neuroptera), hymenopterans (Hymenoptera), dipterans (Diptera) and lepidopterans (Lepidoptera). The most widespread representatives of 6 orders of insects are Diptera, Coleoptera, Orthoptera, Homoptera, Hemiptera. Dipterans predominate in all biotopes, their proportion is up to 40 % of all insects. Orthopterans dominate by biomass everywhere. The structure of entomocomplexes in the studied biocenoses has been established: qualitative composition and quantitative characteristics (abundance and biomass). It is shown that the number of Coleoptera is reduced by almost 2.5 times on pastures compared to the control, while for Hemiptera and Orthoptera, on the contrary, increased. Hygrophiles are replaced by more meso- and xerophilous species. A high number of white–banded filly Chorthippus albomarginatus (De Geer, 1773), a well-known pest of farmland, has been recorded in agrocenoses (an order of magnitude higher than in natural meadows). The disappearance of grasshoppers (indicators of reserved state) from communities has been noted as the anthropogenic load on biogeocenoses increases. The tendency of changes in the structural and functional organization of entomocomplexes has been revealed, it manifests itself in the change of species differing in hygropreferendum. Thus, hygrophilous stenobionts are replaced by mesophilic and mesoxerophilic species and elements of steppe (Stenobothrus lineatus), semi-desert (Gomphocerippus rufus) and even desert (Bryodemella tuberculata) fauna. The bioindicational significance of individual groups and species of insects, demonstrated on orthopterans, has been established.
Keywords: Belarusian Polesie; drainage reclamation; transformed lands; open biocenoses; insects; orthopterans; environmental indicator species; bioindication assessment of the territory